Supplementary dataset to the article " SnRK1 subcellular localization modulate TOR signaling and salt stress tolerance in Arabidopsis thaliana leaves" [Conjunto de datos] - Lando, Ana Paula; Maritano, Paula Catalina; Barbieri, Giuliano; Daloso, Danilo; Martínez-Noël, Giselle; Rodriguez, Marianela (IFRGV - CIAP, INTA, 2026)
Supplementary data set to the article "SnRK1 subcellular localization modulate TOR signaling and salt stress tolerance in Arabidopsis thaliana leaves."